2021
DOI: 10.3390/rs13081432
|View full text |Cite
|
Sign up to set email alerts
|

Two Severe Prolonged Hydrological Droughts Analysis over Mainland Australia Using GRACE Satellite Data

Abstract: In recent years, many droughts have happened over mainland Australia, especially the two severe prolonged droughts, from 2006 to 2009 and 2018 to 2020, resulting in serious water scarcity. Therefore, using the Total Storage Deficit Index (TSDI) from the Gravity Recovery and Climate Experiment (GRACE), we analyzed the two severe prolonged droughts from the perspective of the affected area, spatial evolution, frequency, severity and drought driving factors. The results show that the affected area of Drought 2006… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…GRACE data are processed by NASA to generate the Total Water Storage Anomaly (TWSa) dataset, which captures the change in water storage globally in an anomaly format [24]. GRACE data have been used for various applications, such as flood studies [25][26][27][28][29], drought studies [30][31][32][33][34][35], and general hydrologic investigations focusing on regional water storage and trends [36][37][38]. Recent research has demonstrated the use of GRACE data for monitoring variations in groundwater storage [39][40][41][42][43] including variations in groundwater depletion in arid and semiarid regions [15,44,45].…”
Section: Grace Datamentioning
confidence: 99%
“…GRACE data are processed by NASA to generate the Total Water Storage Anomaly (TWSa) dataset, which captures the change in water storage globally in an anomaly format [24]. GRACE data have been used for various applications, such as flood studies [25][26][27][28][29], drought studies [30][31][32][33][34][35], and general hydrologic investigations focusing on regional water storage and trends [36][37][38]. Recent research has demonstrated the use of GRACE data for monitoring variations in groundwater storage [39][40][41][42][43] including variations in groundwater depletion in arid and semiarid regions [15,44,45].…”
Section: Grace Datamentioning
confidence: 99%
“…Most of these changes are related to large-scale surface and subsurface water resource variations and can elucidate regional hydrological changes (Rodell & Reager, 2023). These changes may be climate-driven, such as the melting of the ice caps or long-term droughts (Tapley et al, 2019), or man-made, such as groundwater withdrawal (Adams et al, 2022;Richey et al, 2015;Rodell et al, 2018;Wang et al, 2021).…”
Section: Hydrogeodesy In a Nutshellmentioning
confidence: 99%
“…(1) the Amazon river basin, which is characterized by the largest hydrological changes in the July 2008 to May 2009 period [50], (2) the Northern Territory of Australia, which is characterized by significant inter-annual variations of TWS in the July 2008 to May 2009 period [28], and (3) a region of Central Europe, which is often presented as the one with insignificant hydrological changes [2]. The area of the Northern Territory of Australia is defined after [51]. Central Europe is defined according to [52].…”
Section: Test Period: Artificial Gapmentioning
confidence: 99%